Photovoice: Fostering Speaking Skills among EFL Students in Kampung Inggris Transmigration through Storytelling - L, Salsabila; Fajar, Ahmad; Ikhsan, Muhammad Miftahul; Fitringga, Muhammad Amar; Aisyah, Siti; Nasrullah, Nasrullah (Universitas Negeri Medan, 2023)
Storytelling have already integrated in learning speaking with many advantages, the researchers apply it among EFL (English as a Foreign Language) students in Kampung Inggris Transmigration to fostering students' speaking skills. Utilizing the Photovoice methodology and the SHOWeD method, the study systematically explores the use of storytelling in language learners' speaking abilities. Participants of this study were 5 tutors and 30 students from two EFL classes in Kampung Inggris Transmigrasi. The findings highlight the pivotal role of storytelling in creating a dynamic and engaging learning environment that encourages active participation and collaboration. This research contributes to the field of language education by emphasizing the significant influence of storytelling on developing effective speaking skills in EFL students, offering insights into innovative methodologies for language acquisition.Keywords: Speaking Skills, Storytelling, and EFL Students